Sodium Butyrate Alleviates Lipopolysaccharide-Induced Inflammatory Responses by Down-Regulation of NF-κB, NLRP3 Signaling Pathway, and Activating Histone Acetylation in Bovine Macrophages - Jiang, Liqiang; Wang, Jingjing; Liu, Ziyi; Jiang, Aimin; Li, Shuangqiu; Wu, Di; Zhang, Yong; Zhu, Xingyi; Zhou, Ershun; Wei, Zhengkai; Yang, Zhengtao (Frontiers in Veterinary Science, 2020)
Sodium butyrate is the sodium salt of butyric acid, which possesses many biological functions including immune system regulation, anti-oxidant and anti-inflammatory ability. The present study was designed to elucidate the anti-inflammatory effects and mechanisms of sodium butyrate on lipopolysaccharide (LPS)-stimulated bovine macrophages. The effect of sodium butyrate on the cell viability of bovine macrophages was assayed by using the CCK-8 kit. Quantitative real-time PCR (qRT-PCR) was used to detect the gene expression of interleukin-6 (IL-6), interleukin-1β (IL-1β), cyclooxygenase-2 (COX-2), and inducible Nitric Oxide Synthase (iNOS). NF-κB, NLRP3 signaling pathway and histone deacetylase were detected by western blotting. The results showed that sodium butyrate had no significant effect on cell viability at 0-1 mM, and inhibited LPS-induced IL-6, IL-1β, COX-2 and iNOS expression. Moreover, sodium butyrate suppressed LPS (5 μg/ml)-stimulated the phosphorylation of IκB and p65, inhibited the deacetylation of histone H3K9, and has also been found to inhibit protein expression in NLRP3 inflammasomes. Thus, our finding suggested that sodium butyrate relieved LPS-induced inflammatory responses in bovine macrophage by inhibiting the canonical NF-κB, NLRP3 signaling pathway and histone decetylation, which might be helpful to prevent cow mastitis.